Intercultural competency in public health: a call for action to incorporate training into public health education - Julia eFleckman; Mark eDal Corso; Shokufeh eRamirez; Maya eBegalieva; Olivia eBrown; Carolyn eJohnson (Frontiers Media S.A., 2015)
Due to increasing national diversity, programs addressing cultural competence have multiplied in U.S. medical training institutions. Little progress has been made to translate cultural competency training from the clinical setting into the public health setting where the focus is on population-based health, preventative programming, and epidemiological and behavioral research. The need for culturally relevant public health programming and culturally sensitive public health research is more critical than ever. Awareness of differing cultural roles needs to be included in all processes of planning, implementation and evaluation. In focusing on community-based health program planning and research, cultural competence implies that it is possible for public health professionals to completely know another culture, whereas intercultural competence implies it is a dual-sided process. Public health professionals need a commitment toward intercultural competence and skills that demonstrate flexibility, openness and self-reflection so that cultural learning is possible. In this article, the authors recommend a number of elements to develop, adapt and strengthen intercultural competence education in public health educational institutions.